FACTORS ASSOCIATED WITH TUBERCULOSIS-DIABETES MELLITUS COMORBIDITY: Faktor-faktor yang Berhubungan dengan Komorbiditas Tuberkulosis-Diabetes Mellitus - Nugrahaeni, Dyan Kunthi; Kusumasari, Ika; Budiana, Teguh Akbar; Mauliku, Novie Elvinawaty (Universitas Airlangga, 2025)
Background: The double burden disease refers to the increase of communicable and non-communicable disease, such as comorbidity tuberculosis (TB) with diabetes mellitus (DM). If not treated properly and managed, tuberculosis can lead to comorbidity with diabetes mellitus. Purpose: This research aims to determine factors associated with tuberculosis-diabetes mellitus comorbidity. Methods: Research design used case-control study, sample cases are TB patients with DM as many as 15 people, while sample control is TB patient without DM as many as 30 people. Independent variables include age, education, occupation, TB severity, body mass index, and quality of life, while the dependent variable is comorbidity TB-DM. The instrument used the World Health Organization’s Quality of Life Brief Version (WHOQOL-BREF). Data analysis was performed utilizing the Chi-Square test and Independent T-test. Results: This study’s findings indicated that the variable age (p= 0.011; OR= 6; 95% CI= 1.39-25.85), education (p=0.03; OR= 4.12; 95% CI= 1.06-16.03), TB severity (p= 0.02; OR= 4.57; 95% CI= 1.18-17.67), and quality of life domains were significantly related to TB-DM with comorbidity: physical (p=0.00; OR=42.25; 95%CI=6.82-261.61), psychological (p=0.03; OR=4; 95% CI=1.07-14.89) and environmental domain (p=0.01; OR=10.54; 95% CI=1.06-105.03). Conclusion: Factors influencing comorbidity between TB-DM include age, education level, TB severity and quality of life. Enhancing immunity in TB patients is essential to reduce the severity of TB and comorbidity of TB-DM, with recommendations for support from family, parents, children, and friends to improve the quality of life for those with TB-DM.